EFEKTIVITAS EDUKASI BOOKLET TERHADAP PENGETAHUAN DAN SIKAP IBU BALITA TENTANG IMUNISASI DASAR LENGKAP : Edukasi Booklet Terhadap Pengetahuan dan Sikap Ibu Balita Tentang Imunisasi - Reni Purwasih; Fajar Sari Tanberika; Lisviarose; Fatma Nadia (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2025)
ABSTRACT Mothers' knowledge of basic immunizations for children causes fear of reactions. Immunization rates in Riau Province reached 21% in 2022, and some children were still unimmunized. The health information booklet, a booklet combining text and images, can be taken home for repeated reading and storage. This research was quantitative, pre-experimental, with a one-group pretest-posttest design. The purpose of this study is to determine the effectiveness of booklet education on the knowledge and attitudes of mothers of toddlers regarding complete basic immunization at the Teratai Posyandu, Ringin Village, the working area of ​​the Batang Gansal Community Health Center, Indragiri Hulu Regency in 2025. The results of the univariate study showed an increase in the average knowledge score after being given an intervention of 3.67 and an increase in the average attitude score after being given an intervention of 11.79. The bivariate results used the Wilcoxon Signed Rank Test, knowledge with a p-value of 0.028 and 0.042. This bivariate analysis used the Wilcoxon Wilcoxon Test which showed an increase in knowledge after being given routine immunization education using booklet media for 17 respondents. It is hoped that further researchers can develop media related to mothers' knowledge and attitudes towards complete basic knowledge, for example with leaflets, banners, etc.